Durasi Pencapaian Anestesi Stadium 3 Pada Pasien General Anesthesia Di RSUD Hj. Anna Lasmanah Banjarnegara - Ihsan, Muhammad Galih; Budi, Martyarini; Yudono, Danang Tri (JUKEJ : Jurnal Kesehatan Jompa, 2025)
General anaesthesia is an important part of surgery that requires the achievement of stage 3 anaesthesia effectively and safely. The duration of achieving this stage is influenced by several factors, including age, body mass index (BMI), and physical status based on the American Society of Anesthesiologists (ASA) classification. This study aims to describe the duration of achievement of stage 3 anaesthesia stages in patients with general anaesthesia at RSUD Hj. Anna Lasmanah Banjarnegara. This study used a quantitative descriptive design with a cross-sectional approach. A sample of 95 patients undergoing general anaesthesia was selected using accidental sampling technique. Data were collected through direct observation and medical record documentation, then analysed univariately in the form of frequency distribution and percentage. The results showed that the duration of achieving stage 3 anaesthesia was mostly >60 seconds in adult patients (47.3%), ASA II physical status (51,6%), and overweight BMI category (44.2%). Meanwhile, duration ≤60 seconds was more common in elderly and ASA III patients. These findings suggest that age, physical status, and BMI affect the speed of achieving stage 3 anaesthesia. Therefore, adjusting the dose and technique of anaesthesia induction based on patient characteristics is necessary to improve the safety and effectiveness of anaesthesia. Keywords : general anaesthesia, duration of anaesthesia, patient characteristics